Low-cost microwave imaging portable device for breast cancer detection. - Aragão, Alexandre de Jesus (2021)
This thesis aims at developing an impulse radar microwave imaging system applied for breast cancer detection. It proposes solutions focusing on realization of low-cost and portable system prototypes. At first, a breast dielectric tissues study is presented. The relevant dielectric constant difference between a tumor and internal breast tissues is simulated in a heterogeneous breast front-end scenario. A 5th derivative Gaussian pulse is applied to an antenna that illuminates the breast model. The reflected signals are collected from a scenario of 32-antenna positions, covering a 360-degree 2D environment. Microwave Imaging is performed using the Delay and Sum confocal algorithm. Into this issue, improvements are proposed to the algorithm, focusing on tumor borders definition and considering that the tumor is mostly located near the glandular tissue in the ductal region, displaced from the breast center. The algorithm robustness is demonstrated using waveform sets generated from numeric, simulated and experimental scenarios. Subsequently, a study of the power loss by the several breast layers is done, pointing a trade-off between operational frequency, tumor resolution and breast depth. A tissues loss scenario have been calculated and simulated. Using these results, a new antenna-breast medium is proposed concerned with dielectric coupling, mechanical flexibility, comfort and hygienic to the patient. Also based on these front-end studies, a phantom is made to mimic the internal breast tissues, using materials with dielectric properties near to the real ones. Finally, a Microwave Imaging role prototype and a handheld system are realized. A low-cost (US$ 150.00) Commercially Available Off-the-Shelf Impulse Radar Ultra Wideband transceiver platform is used to generate and collect the microwave signals. Firmware, software and communication protocol were developed to allow access to the platform via a Personal Computer. The system is mounted using both the proposed antenna-breast coupling and breast phantom. The prototype and handheld tests were performed in a 2D assembly, where backscattered signals were individually collected at 64 positions, and applied to the improved confocal algorithm. Prototype results showed good location precision, high contrast on tumors borders definition with minimum SCR of 2.17 dB and SMR of 13.68 dB. Furthermore, the handheld implementation resulting reconstructed images presented SCR and SMR above 6.00 dB and 28.00 dB, respectively, and tumor location precision below 0.3 cm. For the proposed hardware, considering an average 15.0 cm diameter breast phantom and a 6.4 GHz operational frequency, a 1.0 cm diameter tumor buried 3.0 cm depth in the breast was detected. These results showed the system feasibility which can be distributed in medical offices, stepping up the total of people with access to early breast cancer diagnosis.